Timed Up and Go test score and factors associated with a moderate-to-high risk of future falls in patients scheduled for vascular surgeries—a cross-sectional study - Piotrkowska, Renata; Mędrzycka-Dąbrowska, Wioletta Anna; Tomaszek, Lucyna (Frontiers in Public Health, 2024)
Introduction Peripheral artery and aorta diseases contribute to complex consequences in various areas, as well as increasing physical and mental discomfort resulting from the progressive limitation or loss of functional capacities, in particular in relation to walking, decreased endurance during physical exercise, a drop in effort tolerance, and pain suffered by patients. Limitations in functional capacities also increase the risk of falls. Most falls take place during the performance of simple activities. The aim of this study was to investigate factors associated with moderate-to-high risk of future falls in patients scheduled for vascular surgeries. Methods This cross-sectional study included patients aged 33–87, scheduled for vascular surgeries. Based on the Timed Up and Go test, patients were categorized as having a moderate-to-high (≥ 10 s) or low risk of falls. Multiple logistic regression was carried out to assess the relationship between fall-risk levels and independent sociodemographic and clinical variables. Results Forty-eight percent of patients were categorized as having a moderate-to-high risk of future falls. Females (OR = 1.67; Cl95%: 1.07–2.60) and patients who suffered from hypertension (OR = 2.54; Cl95%: 1.19–5.40) were associated with a moderate-to-high risk of future falls. The Barthel Index correlated negatively (OR = 0.69; Cl95%: 0.59–0.80), while age correlated positively with fall-risk levels (OR = 1.07; Cl95%: 1.02–1.12). Conclusion Factors that may be associated with a moderate-to-high risk of future falls in patients scheduled for vascular surgeries include age, female gender, hypertension, and the Barthel Index.